Homoeopathy in Relation of Psychological factors that affect Physical Conditions (Homoeopathy for All, 2024)
Psychosomatic diseases which are  also called as psychological Factors  that affect Physical condition by  DSM-V. These are the conditions by  where psychological factors (stress,  anxiety) triggered or exacerbated  physical illnesses. Stress has a strong  influence on mind and emotions  thereby affect the functioning of  mind and physical body. The article  shows how Homoeopathic approach  is best for psychosomatic diseases,  how the principle of homoeopathy  helps in understanding the  psychosomatic diseases because  when homoeopathy cures a normal  individual, the deeper side of his  being i.e., emotions, the will and the  understanding or the rational mind  comes into equilibrium i.e., health
Keywords: Psychosomatic; Psychophysiological; Homoeopathy; Holistic treatment